Two new species of Sierola Cameron (Hymenoptera: Bethylidae) from New Zealand and Australia. Issue 1 (2nd January 2019) - Magnacca, Karl N.
ABSTRACT: The bethylid genus Sierola is large and widespread, but largely undescribed. Two new species are described from New Zealand, the endemic Sierola houdiniae sp. nov. and presumed adventive S. thorpei sp. nov. The Australian S. antipoda Ashmead is also re-described from the type and characters to distinguish it from S. houdiniae given. http://zoobank.org/urn:lsid:zoobank.org:pub:8ADE582D-A372-4AF0-8FB2-97AFF03F1B39